Elaine Steinbeck at Grapes of Wrath 50th Anniversary Party - unknown:::Creator::::::::::::
Elaine Steinbeck laughing with an unidentified man at The Grapes of Wrath 50th Anniversary celebration at the '21' Club on 21 West 52nd Street in New York City. This party was attended by Douglas Fairbanks, Junior; Elia Kazan; Arthur Schlesinger, Junior; Edward Albee; and Tom Guinzburg (son of Steinbeck's publisher).